Discovery of 1, 3-dihydro-2, 1, 3-benzothiadiazole 2, 2-dioxide analogs as new RORC modulators. Issue 9 (1st May 2015) - Muegge, Ingo; Collin, Delphine; Cook, Brian; Hill-Drzewi, Melissa; Horan, Josh; Kugler, Stanley; Labadia, Mark; Li, Xiang; Smith, Lana; Zhang, Yunlong
Graphical abstract